Image reconstruction comparison on quantity of ultrasonic transceiver tomography in non-invasive imaging of liquid / gas flow - Pusppanathan, Jaysuman (Penerbit UTM, 2010)
Currently, besides ultrasonic there are a number of tomography techniques available for studying complex multiphase phenomena. These include electrical tomography (Impedance, Capacitance and Resistance), optical, positron emission tomography (PET), X-ray, magnetic resonance imaging (MRI), ultrasonic and others. Each of these techniques has its advantages, disadvantages and limitations but each of it has common purpose to analyze measured data. The best way is by reconstructing images from acquired data.